Development of Learning Media Simulation of Automatic Garden Lights Using the Proteus Application - Renda Sandi Saputra (Research Collaboration Community (RCC), 2022)
With so many garden lights, gardeners often struggle to turn on or turn on garden lights manually, this study aims to make it easier for park officers or gardeners to turn on or turn off garden lights practically. Automatic garden light is a lighting system that runs automatically, this system can use light sensors such as LDR (Light Dependent Resistor), photodiode and others. However, this circuit system can also use a timer that has been set in time when the circuit or garden lights will turn on and off, this can happen because there is an automatic switch circuit that utilizes the characteristics of one of the light sensors, namely the LDR sensor whose resistance value can change according to Light intensity. During the day, the resistance value of the LDR will be very high and even reach its maximum value of 10k , this makes the current flowing to the base of the transistor very small, to activate the transistor 2N3055 a minimum voltage of 0.9V is needed to the base of the transistor. Because the resistance of the LDR is very large, the voltage that enters the base of the transistor will be very small or even non-existent so that the transistor is like an open switch and does not flow current. One type of automatic switch that is widely used today is a light switch with a light sensor, where the switch will turn off and on automatically because it is affected by the intensity of the light around it. For example, at night, we don't need to press the switch to turn on the lights, because the lights will turn on automatically. The results of this study indicate that the simulation experiment of garden lights using the Proteus application went well, the use of simulation using Proteus also aims to make it easier for us to understand an electronic component and how it works.